Fertility Intentions and Perspectives on Contraceptive Involvement Among Low‐Income Men Aged 25 to 55. Issue 3 (26th August 2019) - Campbell, Anthony D.; Turok, David K.; White, Kari
Abstract : CONTEXT: Unintended pregnancy is disproportionately reported by low‐income individuals in the United States, and studies of men's roles in preventing pregnancy have largely focused on adolescents and young adults. Less is known about the pregnancy‐related attitudes and behaviors among men older than 24, who are involved in the majority of pregnancies ending in a birth. METHODS: Between December 2015 and August 2016, in‐depth interviews were conducted with 26 low‐income men in Alabama who were aged 25–55, were sexually active and did not want more children. Interviews explored men's reasons for not wanting more children, their contraceptive knowledge and attitudes, and their involvement in contraceptive decision making. Transcripts were examined using content analysis to identify themes related to men's perspectives about preventing pregnancy and using contraceptives. RESULTS: Participants' motivations to prevent a pregnancy centered primarily on their age and financial circumstances. Most men had limited contraceptive knowledge and perceived their risk of causing a pregnancy to be low, regardless of method use. Few men engaged in decisions about contraceptive use, despite their beliefs that men and women had a shared responsibility to prevent pregnancy. Although some men were interested in vasectomy, a few were hesitant about undergoing the procedure because they might want to have children later if their life circumstances changed, and others worried that vasectomy might affect sexual performance. CONCLUSIONS: Some low‐income adult men were uncertain about their pregnancy desires, and many lacked contraceptive knowledge that would help them avoid unwanted pregnancy. Research is needed to identify the types of programs that could effectively promote men's constructive engagement in preventing pregnancies over their reproductive life course.